A contribuição do estágio supervisionado para a formação reflexiva do pedagogo - Brasil, Maria Ghisleny de Paiva (2010)
This study aims to investigate the contribution of supervised training for training reflective of the students in the service of pedagogy course of the Vocational Training Program for Basic Education - PROFORMAÇÃO Universidade Estadual do Rio Grande do Norte / Campus Avançado Professor João Ismar de Moura - CAJIM Patu City / RN. Based on studies of Schon (2000), Alarcão (2003), Pimenta (1994, 2000), Tardif (2002) Ibiapina (2008) among others have adopted a theoretical framework which have been focusing on studies concerning the formation of the reflective teacher, in perspective also contribute to the professionalization of teachers. The study falls within the qualitative approach of educational research and the methodology chosen has characteristics of a collaborative research. In the process, we used the following instruments: individual and group interview, sitting reflective observation, videoformação, material prescribed personal documents. The relevance of this research is to highlight the contribution of reflexive perspective in the teaching profession for: knowledge of teachers, teacher professional development, relationship between theory and practice, collective work, school and university as a place of training. These findings indicate that: a) the stage for advanced teacher becomes a teacher action research, seeking to (re) signification practices, b) the stage still presents itself as an activity limited to the applicability of the theories, hence the need for dialogic relations between theory and practice in education, requiring their redefinition c) despite experiencing an in-service training, the students still need information to enable them to link theory to practice, but understand its importance, d) a collaborative discussion can be a strategy that encouraged and implemented, is likely to be an alternative to the consolidation of training reflective e) It is important to the collective action of teachers in the school and the university as an opportunity for development of the reflective process f) the students-teachers still do not understand what is reflection and not experiencing it, but realizes the need to change the thinking and way of acting, g) there are conflicts between the teacher's knowledge of the students, teachers and the actions constituting the real, creating contradictions between saying and doing training